Fibroblast Growth Factor 23 Expression Is Increased in Multiple Organs in Mice With Folic Acid-Induced Acute Kidney Injury - Egli-Spichtig, Daniela; Zhang, Martin Y. H.; Perwad, Farzana (Frontiers in Physiology, 2018)
Fibroblast growth factor 23 (FGF23) regulates phosphate homeostasis and vitamin D metabolism. In patients with acute kidney injury (AKI), FGF23 levels rise rapidly after onset of AKI and are associated with AKI progression and increased mortality. In mouse models of AKI, excessive rise in FGF23 levels is accompanied by a moderate increase in FGF23 expression in bone. We examined the folic acid-induced AKI (FA-AKI) mouse model to determine whether other organs contribute to the increase in plasma FGF23 and assessed the vitamin D axis as a possible trigger for increased Fgf23 gene expression. Twenty-four hours after initiation of FA-AKI, plasma intact FGF23 and 1,25(OH)2D were increased and kidney function declined. FA-treated mice developed renal inflammation as shown by increased Tnf and Tgfb mRNA expression. Fgf23 mRNA expression was 5- to 15-fold upregulated in thymus, spleen and heart of FA-treated mice, respectively, but only 2-fold in bone. Ectopic renal Fgf23 mRNA expression was also detected in FA-AKI mice. Plasma FGF23 and Fgf23 mRNA expression in thymus, spleen, heart, and bone strongly correlated with renal Tnf mRNA expression. Furthermore, Vdr mRNA expression was upregulated in spleen, thymus and heart and strongly correlated with Fgf23 mRNA expression in the same organ. In conclusion, the rapid rise in plasma FGF23 in FA-AKI mice is accompanied by increased Fgf23 mRNA expression in multiple organs and increased Vdr expression in extra osseous tissues together with increased plasma 1,25(OH)2D and inflammation may trigger the rise in FGF23 in FA-AKI.